Comparison of the Prevalence of Infantile Colic Between Pediatric Migraine and Other Types of Pediatric Headache. (August 2020) - Levinsky, Yoel; Eidlitz-Markus, Tal
Background/Objective: The International Headache Society lists infantile colic under "episodic syndromes that may be associated with migraine" in the ICHD3-beta version of its classification of headache disorders. The aim of this study was to examine whether this association is specific to migraine or applies to all pediatric headache types. Methods: A cross-sectional historical study was conducted including 219 patients aged 3-18 years who presented to a tertiary pediatric headache clinic in 2016-2017. Parents were asked a series of questions to determine if their child had had infantile colic as defined in the ICHD3-beta version. The prevalence of a positive history of colic was compared between children diagnosed with migraine or other primary headache types. Results: There were 132 girls (60.2%) and 87 boys (39.8%) of mean age 12.8 ± 3.48 years at presentation. Migraine headache was diagnosed in 170 patients (77.6%) and other types primary of headache (9 in total) in 49 patients (22.3%). Fifty-one patients had a history of infantile colic. They included 45 patients in the migraine group (26.5%) and 5 in the comparison groups (10.2%); the difference in the rate of colic was statistically significant ( P = .0196; OR 3.17, 95% CI 0.1.17-6.17). There was no association of specific migraine parameters or symptoms with infantile colic. Conclusion: There appears to be an association of infantile colic with pediatric migraine but not with other types of pediatric headache. These findings reinforce the theory that infantile colic has common pathogenic roots with migraine.